Nurses' perceptions of medication administration safety in public hospitals in the Gauteng Province: A mixed method study - Alwiena J. Blignaut; Siedine K. Coetzee; Hester C. Klopper; Suria M. Ellis (Elsevier, 2022)
Background: Limited data on factors perceived to impact on medication administration errors and possible solutions to such errors in low- and middle-income settings like South Africa is available. Methods: A mixed-methods research design was used. Data were gathered from 280 medication administrators using self-report surveys, and 15 nursing unit managers using semi-structured individual interviews. Results: Causes of medication error related to communication, human, environmental and medication factors were considered to have a moderate risk. Workload (M = 3.39; SD 0.91), stock problems (M = 3.18; SD 0.96) and illegible prescriptions (M = 3.05; SD 1.09) pose the greatest threats to medication administration safety. Most participants (n = 184; 71.1 %) agreed that medication errors never or rarely occurred in their units. The majority of respondents graded overall patient safety as excellent or very good (n = 161; 61.5 %). On safety culture, nurses felt that they are actively attempting to improve medication safety (n = 239; 90.5 %), that people support one another in the unit (n = 216; 80 %), and that their procedures and systems are good at preventing errors (n = 210; 80.2 %). Participants felt that medication administration errors were rarely reported, mostly due to fear and administrative response. Qualitative findings supported the quantitative data, adding knowledge, skill and attitude of staff as further threats to medication administration safety. Adherence to protocols, auditing, education and training, collaboration and support, communication, awareness of changes, resource management and time management were identified as possible mitigating factors. Conclusions: Solutions aimed at preventing medication errors should be based on causes identified within a specific context. In the Gauteng Province, multidisciplinary collaboration and communication; support of nurses by the hospital administration; hospital systems, procedures and initiatives; better resource management and improved pharmacological training could be seen as the foundation for improved medication administration safety.